1996
DOI: 10.1097/00005392-199604000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Bladder Tumors in Spinal Cord Injury Patients

Abstract: An indwelling urinary catheter and a history of bladder stones are statistically significant risk factors. Cytology and biopsy are complimentary in the evaluation of urothelial malignancy in this population. A high index of suspicion and thorough evaluation are needed in spinal cord injury patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
13

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 9 publications
0
41
0
13
Order By: Relevance
“…2,16,17 Moreover, long-term indwelling catheter can lead to bladder cancer. 18 Catheters should be removed before the onset of irreversible complications. Some patients do not agree for SCIC or sphincterotomy (men) despite continuous improvements of appliances.…”
Section: Discussionmentioning
confidence: 99%
“…2,16,17 Moreover, long-term indwelling catheter can lead to bladder cancer. 18 Catheters should be removed before the onset of irreversible complications. Some patients do not agree for SCIC or sphincterotomy (men) despite continuous improvements of appliances.…”
Section: Discussionmentioning
confidence: 99%
“…14 The exact mechanisms of carcinogenesis are not understood but are likely related to the repeated chronic irritation caused by a foreign object resulting in metaplasia, then dysplasia, and finally carcinoma. One theory relating chronic cystitis to BC, particularly squamous cell carcinoma, implicates nitric oxide and NNCs, whose levels are raised in chronic cystitis associated with chronic indwelling catheterization.…”
Section: Schistosomiasismentioning
confidence: 99%
“…The following characteristics make particular cancers more suitable than others for screening: 4,5 (a) substantial morbidity and mortality, (b) a high prevalence in a detectable preclinical state, (c) the possibility of e ective and improved treatment because of early detection, and (d) the availability of a good screening test. The screening test must be safe, rapid, inexpen- 8 an occurrence which was noted in this study as well. This suggests that lowstage disease is not readily identi®ed by screening.…”
Section: Discussionmentioning
confidence: 66%
“…The majority of the reported cases of bladder cancer in SCI patients list the tumor stage at the time of diagnosis as T2 or greater, with very few super®cial tumors. 3,8,9 The high stage of the disease at diagnoses would argue for heightened surveillance. But the rapidly progressive nature of the disease, seen in two patients during this study who died within a year of diagnosis and reported by others, 10,11 discounts the utility of practical screening measures.…”
Section: Discussionmentioning
confidence: 99%